(untitled) (Development Service Industry Management, 2023)
In the presented article, various aspects of digital transformation in the contemporary business environment are explored. The primary focus is on analyzing key strategies of digital transformation, methods of their implementation, and addressing potential challenges in this process. The article aims to highlight both successful and unsuccessful experiences of companies in this context, emphasizing the importance of a strategic approach and organizational flexibility. Based on the conducted analysis, the article provides valuable recommendations for organizations intending to adapt effectively to the new realities of the digital era and achieve successful transformation in a competitive business environment. The authors systematically examine diverse nuances of digital transformation, paying attention to both positive aspects and possible difficulties that may arise during implementation. Specifically, the importance of developing clear strategies reflecting the organization’s main goals and tasks in the context of digital transformation is thoroughly discussed. The article also sheds light on the practical experiences of companies that have already undergone digital transformation, particularly emphasizing successful initiatives and important lessons learned from unsuccessful attempts. This allows readers to consider specific examples and avoid common pitfalls. In conclusion, the article stands out for its practical orientation, and the provided recommendations serve as a valuable guide for organizations aiming not only to implement digital technologies but also to achieve effective and competitive positioning in the modern business environment.